Impact of minority perceived discrimination on resistance to innovation and moderating role of psychological distress: Evidence from ethnic minority students of China - Wang, Junwei; Shaheen, Musarat (Frontiers in Psychology, 2022)
Ethnic minority groups usually face discrimination in the form of prejudice and stereotypes. The self-esteem and psychological well-being of ethnic minority groups are adversely impacted by the prejudice and discrimination behavior of others. The perceived discrimination unfavorably influences the attitude and behavior of ethnic minority groups, which in turn develops resistance to innovation among them. With the support of social exchange theory, this study hypothesized that perceived discrimination positively enhances resistance to innovation and job dissatisfaction for empirical investigation. The current study also proposes that job dissatisfaction positively correlates with resistance to innovation. This study further assumes the mediating role of job dissatisfaction and moderating role of psychological distress forfurther investigation. For empirical investigation, the present study collected the data from 328 Ethnic Minority Students of various Chinese universities through a structured questionnaire method using a convenient sampling technique. This study applied partial least square structural equation modeling (PLS-SEM) for empirical examination using Smart PLS software. The findings confirm that perceived discrimination positively correlates with resistance to innovation and job dissatisfaction, respectively. It is also verified that perceived discrimination positively impacts job dissatisfaction. The results further interpreted that job dissatisfaction mediates the relationship between perceived discrimination and resistance to innovation. Additionally, the findings revealed that psychological distress does not moderate the relationship between perceived discrimination and resistance to innovation; however, psychological distress moderates the relationship between job dissatisfaction and resistance to innovation. The findings serve the organizations by pointing out the role of perceived discrimination on job dissatisfaction. This study also provides valuable theoretical and practical implications.